Risk Factors for the 90-Day Prognosis Of Severe Heat Stroke: a Case-Control Study. Issue 1 (January 2021) - Zhong, Li; Wu, Ming; Liu, Zheying; Liu, Yan; Ren, Guangli; Su, Lei; Liu, Zhifeng
ABSTRACT: Background: Severe heat stroke is a clinical syndrome caused by host stress dysfunction due to heat stress and subsequent life-threatening organ dysfunction. We aimed to explore the early risk factors affecting the 90-day prognosis of severe heat stroke patients. Methods: A case-control study was used to retrospectively analyze the clinical data of 117 severe heat stroke patients admitted to the intensive care unit of the General Hospital of Southern Theater Command from April 2014 to May 2019. The risk factors affecting the 90-day mortality of the patients were analyzed, and subgroup analysis was performed comparing the complete recovery and the sequelae subgroups of survivors. Results: Thirteen patients (11.1%) died within 90 days. The multivariate Cox risk regression model showed that cooling time (HR 4.87; 95% CI: 1.94–12.18; P = 0.001), heart rate (HR 1.04; 95% CI: 1.01–1.09; P = 0.027), and Sequential Organ Failure (SOFA) score (HR 1.41; 95% CI: 1.21–1.65; P < 0.001) were independent risk factors affecting the survival of patients. The area under the Receiver Operating Characteristic (ROC) curve of the combination of cooling time, heart rate, and SOFA score for the prediction of mortality due to severe heat stroke was 98.1% (95% CI 0.957–1.000, P < 0.001), the sensitivity was 96.2%, and the specificity was 92.3%. Conclusions: The longer the cooling duration, the faster the heart rate at admission, and the higher the SOFA score, the lower the 90-day survival rate was. These three indicators can be used in combination to predict 90-day mortality and poor prognosis in patients with severe heat stroke. Abstract : Supplemental Digital Content is available in the text